(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Covid-19 vaccination is considered the only effective tool against the pandemic. To achieve public health goals, some countries, including ours, considered making it mandatory. However, the imposition of a mandatory vaccination represents a significant implication on the exercise of fundamental human rights. On 8 April 2021, the HUDOC ruled on the mandatory vaccination for the protection of the rights of the most vulnerable people. This work aims to give an analysis of main legal and ethical issues focused on this case that should be taken in consideration by the States before assessing the need for mandatory vaccination.